Wrecked : unsettling histories from the graveyard of the Pacific - Thrush, Coll-Peter, 1970- (Emil and Kathleen Sick lecture-book series in western history and biography., 2025)
"The Northwest Coast of North America is a treacherous place. Unforgiving coastlines, powerful currents, unpredictable weather, and features such as the notorious Columbia River bar have resulted in more than two thousand shipwrecks, earning the coastal areas of Oregon, Washington, and Vancouver Island the moniker "Graveyard of the Pacific." Beginning with a Spanish galleon that came ashore in northern Oregon in 1693 and continuing into the recent past, Wrecked includes stories of many vessels that met their fate along the rugged coast and the meanings made of these events by both Indigenous and settler survivors and observers. Commemorated in museums, historical markers, folklore, place-names, and the remains of the ships themselves, the shipwrecks have created a rich archive. Whether in the form of a fur-trading schooner beached in 1811 or an almost-empty tanker broken on the shore in 1999, shipwrecks on the Northwest Coast open up conversations about colonialism and Indigenous persistence. Thrush's retelling of shipwreck tales highlights the ways in which the three central myths of settler colonialism-the disappearance of Indigenous people, the control of an endlessly abundant nature, and the idea that the past would stay past-proved to be untrue. As a critical cultural history of this iconic element of the region, *Wrecked* demonstrates how the history of shipwrecks reveals the fraught and unfinished business of colonization on the Northwest Coast"--